Entre bandidos e vítimas: as representações no Itatiaia Patrulha - Fabiola Carolina de Souza (2014)
The aim of this work is to investigate the construction of the villain and victim in Itatiaia Patrulha. For the study of the program, we dont adopt the sensationalist perspective but we identify the Itatiaia Patrulha as a popular radiojornal, which brings several elements of popular culture in its journalistic narrative. We discuss the relationship between media and violence and more specifically its role as a developer of representations of violence. Furthermore, our study provides a brief overview of the history of radio journalism in Brazil and in the state of Minas Gerais. We also discuss about the features and radio language. The notions of interaction, performance, framing and footing were important to our analysis, because they helped us to identify the role of villain and victim in the program as well as the values present in Itatiaia Patrulha. We chose to analyze five programs in the period from 22 to 26 April 2013. We organized the analysis in two axes: content analysis, in which we mapped the program and depth analysis, in which we chose six cases with the goal to understand how the journalistic narrative offers placements to their listeners and interviewed.